2019
DOI: 10.3389/fphar.2019.01305
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Mangostin Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice Partly Through Activating Adenosine 5′-Monophosphate-Activated Protein Kinase

Abstract: Background: Pulmonary fibrosis (PF) is a devastating interstitial lung disease and characterized by an abnormal accumulation of extracellular matrix (ECM). Nintedanib (NDN) and pirfenidone are two approved therapies for PF, but their potential side-effects have been reported. Recently, the use of natural supplements for PF is attracting attention. Alpha-mangostin (α-MG) is an active xanthone-type compound isolated from the nutritious fruit mangosteen. Purpose: In the present study, the potential effect and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…After intra-tracheal instillation of BLM, significant weight loss, survival rate reduction and increased wet/dry weight ratio of lung were noticed ( Figures 1A–C ). The seventh day after BLM administration is considered to be the beginning of the fibrotic phase ( Li et al, 2019 ), FIS was intragastrically administered at day 7 for 21 days. BLM-induced weight loss and the increase in the wet/dry weight ratio were attenuated by FIS administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After intra-tracheal instillation of BLM, significant weight loss, survival rate reduction and increased wet/dry weight ratio of lung were noticed ( Figures 1A–C ). The seventh day after BLM administration is considered to be the beginning of the fibrotic phase ( Li et al, 2019 ), FIS was intragastrically administered at day 7 for 21 days. BLM-induced weight loss and the increase in the wet/dry weight ratio were attenuated by FIS administration.…”
Section: Resultsmentioning
confidence: 99%
“…Massive collagen secreted by myofibroblasts is the major source of ECM, while α -SMA is a biomarker protein of myofibroblasts ( Li et al, 2019 ). HYP is one of the main components of collagen.…”
Section: Resultsmentioning
confidence: 99%
“…26) Similarly, our data showed that α-man inhibited TGF-β-induced myofibroblast differentiation in cultured cardiac fibroblasts Periostin reportedly plays an important role in promoting collagen fibrogenesis and its overexpression has been observed in several heart diseases beside to HF. 27) Other researchers have described the protective effect of α-man on pulmonary and liver fibrosis, demonstrated through the reduced expression α-SMA, a myofibroblast marker protein. 28,29) The present study demonstrated the therapeutic effect of α-man in attenuating myofibroblast differentiation through thesuppression of α-SMA expression at both mRNA and protein levels in cultured cardiac fibroblasts.…”
Section: α-Man Inhibits Tgf-β-induced Fibrosis In Cultured Cardiac Fibroblastsmentioning
confidence: 99%
“…α-MG treatments also reduced the abnormal expression of TGF-β1 and the phosphorylation of Smad 2/3 in the lungs. Moreover, α-MG alleviates the process of fibrogenesis by promoting AMPK-mediated inhibition of NOX4 expression and TGF-β1-induced trans-differentiation of lung fibroblast [ 157 ].…”
Section: Natural Products Against Pulmonary Fibrosis With Specific Me...mentioning
confidence: 99%